HUBUNGAN KARAKTERISTIK PASIEN, PROSEDUR, DAN PENYAKIT PENYERTA DENGAN BIAYA LANGSUNG MEDIS PADA PASIEN RAWAT INAP JANTUNG KORONER - Wahyuni, Rita Tri; Witcahyo, Eri; Herawati, Yennike Tri (UI Scholars Hub, 2023)
Coronary heart disease is a catastrophic disease that causes a high burden of medical costs. At Dr.Iskak Tulungagung hospital, coronary heart disease is the disease with the highest cost. The number of coronary heart patients who are hospitalized is also increasing every year. Several Previous studies have shown that the amount of direct medical costs of coronary heart patients reach more than 50% of the total costs of treatment. Therefore, it is necessary to do research on the factors associated with the increasing direct medical costs of coronary heart patients. The purpose of this study was to analyze the factors that influence the amount of direct medical costs in coronary heart inpatients which include: relationship between patient characteristics, medical procedures, and comorbidities with direct medical costs in coronary heart inpatients. This analytical study used a cross sectional design. The research sample was a coronary heart inpatient at Dr.Iskak Tulungagung Hospital who met the inclusion and exclusion criteria, namely 125 samples. Sampling with systematic random sampling. Data were analyzed using Spearman Rho test and Eta test. The results showed that most of the patients were aged 56-65 years, the majority were men with the length of hospitalization mostly for ≤ 3 days. The majority underwent invasive procedures and most had comorbidity. The average direct medical cost in 2020 is IDR 26,788,964 while in 2021 it is IDR 31,553,045. The three biggest costs of cath lab costs, drugs, and doctor and nursing actions. Medical procedures and comorbidity are factors related to that affect the amount of direct medical costs.